Post-liberalization markets, export firm concentration, and price transmission along Nigerian cocoa supply chains - Ajetomba, Joshua Olusegun (International Food Policy Research Institute, 2014)
This study examines whether major Nigerian export firms exert market power over Nigerian cocoa farmers in the form of incomplete price transmission. A common indicator of efficient and functioning markets is the presence of a high level of market integration, while a lack of integration could be an indication of private traders’ market power. This study pays special attention to export firms’ pricing behavior in the post-liberalization period. Our analyses are based on (i) monthly firm-level price data from major Nigerian cocoa beans exporting companies and (ii) monthly farm gate prices between 1986 and 2009.